HPLC Quantification of astaxanthin and canthaxanthin in Salmonidae eggs. (14th October 2016) - Tzanova, Milena; Argirova, Mariana; Atanasov, Vasil
Abstract: Astaxanthin and canthaxanthin are naturally occurring antioxidants referred to as xanthophylls. They are used as food additives in fish farms to improve the organoleptic qualities of salmonid products and to prevent reproductive diseases. This study reports the development and single‐laboratory validation of a rapid method for quantification of astaxanthin and canthaxanthin in eggs of rainbow trout ( Oncorhynchus mykiss ) and brook trout ( Salvelinus fontinalis М.) . An advantage of the proposed method is the perfect combination of selective extraction of the xanthophylls and analysis of the extract by high‐performance liquid chromatography and photodiode array detection. The method validation was carried out in terms of linearity, accuracy, precision, recovery and limits of detection and quantification. The method was applied for simultaneous quantification of the two xanthophylls in eggs of rainbow trout and brook trout after their selective extraction. The results show that astaxanthin accumulations in salmonid fish eggs are larger than those of canthaxanthin. As the levels of these two xanthophylls affect fish fertility, this method can be used to improve the nutritional quality and to minimize the occurrence of the M74 syndrome in fish populations.